PENGARUH LATIHAN SPLIT JUMP TERHADAP KEMAMPUAN TENDANGAN LURUS PADA ATLET PENCAK SILAT PERGURUAN IKATAN KELUARGA SILAT PUTRA INDONESIA KERA SAKTI DESA LUBUK SANAI II: The Effect of Split jump Training on Straight Kicking Ability in Pencak Silat Athletes of the Kera Sakti Indonesian Male Silat Family Association School, Lubuk Sanai II Village - ROHMAN, FATQUL; Nelson, Sonya; Nelson, Septri; Fajri, Hadi Pery (Jurnal IKEOR, 2026)
This investigate is driven by the limited straight kick ability of pencak silat athletes from Kera Sakti Indonesian Male Silat Family Association, Lubuk Sanai II Village, especially in the aspects of speed and kick power. This research seeks to assess the impact of split jump training on the straight kick ability of pencak silat athletes. A quasi-expeimental approach was utilized using a one group pretest-posttest design. The population, which simultaneously served as the sample, consisted of 10 male athletes aged 12-14 years selected through a total sampling technique. The research instrument was a straight kick speed test conducted within a 10 second interval. The treatment was administered in the form of split jump training over 16 sessions. Subsequently, data analysis was carried out using the paired sample t-test with a significance level of 0.05. The findings indicate a significant effect of split jump training on straight kick ability, as evidenced by an Asymp. Sig (2-tailed) value of 0.020 < 0.05 and a t-count of 2.815 exceeding the t-table value of 1.833. These findings demonstrate an improvement in athletes straight kick performance following the training intervention. Therefore, it is evident that split jump training significantly enhances the straight kick ability of pencak silat athletes at Perguruan Ikatan Keluarga Silat Putra Indonesia Kera Sakti Desa Lubuk Sanai II.